In compliance with a resolution passed by your honorable body on the 29th instant, requesting certain information from this office concerning the returns of the several Commissioners appointed to revalue the real estate within the State . ([Publisher not identified], 1867)
Auditor's statement on the reevaluation of real estate within the state, by counties.